Joint Power Control and Beamforming for Interference MIMO Relay Channel - Khandaker, Muhammad; Rong, Yue (IEEE, 2011)
In this paper, we consider an interference multiple-input multiple-output (MIMO) relay system where multiple source nodes communicate with their desired destination nodes with the aid of distributed relay nodes. An iterative algorithm is developed to minimize the total source and relay transmit power such that a minimum signal-to-interference-plus-noise ratio (SINR) threshold is maintained at each receiver. The proposed algorithm exploits the network beamforming technique at the relay nodes and the receive beamforming technique at the destination nodes to mitigate the interferences from the unintended sources in conjunction with transmit power control. In particular, we apply the semidefinite relaxation technique to transform the relay transmission power minimization problem into a semidefinite programming (SDP) problem which can be efficiently solved by interior point-based methods. Numerical simulations are performed to demonstrate the effectiveness of the proposed iterative algorithm.